2009
DOI: 10.1128/mcb.01523-08
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros and GATA-1 Combinatorial Effect Is Required for Silencing of Human γ-Globin Genes

Abstract: During development and erythropoiesis, globin gene expression is finely modulated through an important network of transcription factors and chromatin modifying activities. In this report we provide in vivo evidence that endogenous Ikaros is recruited to the human ␤-globin locus and targets the histone deacetylase HDAC1 and the chromatin remodeling protein Mi-2 to the human ␥-gene promoters, thereby contributing to ␥-globin gene silencing at the time of the ␥-to ␤-globin gene transcriptional switch. We show for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 59 publications
4
90
0
Order By: Relevance
“…MEL cells (100,000 to 150,000) or 14.5 dpc fetal liver cells were collected, and staining was performed as previously described (5). Cell morphology was analyzed with a Leica DMRE microscope, and images were acquired with a Qimaging digital camera.…”
Section: Mouse Linementioning
confidence: 99%
See 2 more Smart Citations
“…MEL cells (100,000 to 150,000) or 14.5 dpc fetal liver cells were collected, and staining was performed as previously described (5). Cell morphology was analyzed with a Leica DMRE microscope, and images were acquired with a Qimaging digital camera.…”
Section: Mouse Linementioning
confidence: 99%
“…The absence of GATA-1 in differentiating embryonic stem cells and in mice results in abnormal EryC maturation and massive apoptosis of proerythrobasts (17). Along with GATA-1, the transcription factor Ikaros acts as a developmental stage-specific repressor of ␥-globin genes in EryC (5,7). This repression is not limited to ␥-globin genes, since in primitive and definitive EryC, Ikaros collaborates with GATA-1 to facilitate Gata2 gene repression (5,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of HDAC1 with NE-F4 minimizes its activation potential at the ␥-promoter in fetal erythroid cells (16). During ␥-to ␤-globin switching, HDAC1 and the chromatin remodeling protein Mi-2 contribute to ␥-globin silencing (17). More recently, it was shown that the short chain fatty acid RB7 mediated displacement of HDAC3 and its adapter protein, NcoR (nuclear receptor co-repressor) from the ␥-globin promoter to stimulate transcription (18).…”
mentioning
confidence: 99%
“…During embryonic hematopoiesis, Ikaros is involved in the activation of g-globulin expression in the yolk sac via direct interaction with GATA1 and participation in transcriptional elongation [Bottardi et al 2011]. Yet, Ikaros is then involved in the silencing of g-globin genes during the switch to the adulttype b-globulin expression during fetal development [Bottardi et al 2009]. Loss of Ikaros activity during development of erythroid lineages results in decreased numbers of differentiating erythroid cells with concomitant decrease in transcription of key early erythroid transcription factors such as GATA1 FOG1, EKLF and EPOR [Dijon et al 2008].…”
Section: Ikaros Structurementioning
confidence: 99%